Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have been trying to solve the following PDE:

$Au_{xx} + Bu_{xy} + Cu_{yy} = 0$

In my case, I know that this is an elliptical PDE, that is $B^2 - 4AC < 0$. Does there exists an analytic solution for such problem ? If not, then can you suggest any numerical technique ?

share|cite|improve this question
Don't accept the answers too fast, you may miss the better answer or influence the ambitions of the SE users. I give you a downvote for a leasson. – doraemonpaul Dec 10 '12 at 0:02
up vote 1 down vote accepted

You can always do a linear coordinate change after which the equation is $u_{xx} + u_{yy} = 0$, whose solutions are called harmonic functions. So if $L$ denotes the linear transformation in question, the solutions will be of the form $h(L^{-1}(x,y))$, where $h$ is any harmonic function.

share|cite|improve this answer
I would like to add that if you are working on a nice enough domain (say with $C^1$ boundary) then you can get explicit solutions for this PDE by specifying boundary conditions and using Green's functions. – Alex Youcis Dec 9 '12 at 17:14

Since all terms of the PDE are in same order and constant coefficient, you can use the "factorization method" to solve it:

The auxiliary polynomial of this PDE can be $A\lambda^2+B\lambda+C$ or $C\lambda^2+B\lambda+A$

By factorizing them in $\mathbb{C}$ :

$A\lambda^2+B\lambda+C=A\left(\lambda+\dfrac{B+\sqrt{B^2-4AC}}{2A}\right)\left(\lambda+\dfrac{B-\sqrt{B^2-4AC}}{2A}\right)$ or $C\lambda^2+B\lambda+A=C\left(\lambda+\dfrac{B+\sqrt{B^2-4AC}}{2C}\right)\left(\lambda+\dfrac{B-\sqrt{B^2-4AC}}{2C}\right)$

$\therefore$ the general solution of $Au_{xx}+Bu_{xy}+Cu_{yy}=0$ is $u(x,y)=f_1\left(2Ay+\left(B+\sqrt{B^2-4AC}\right)x\right)+f_2\left(2Ay-\left(B+\sqrt{B^2-4AC}\right)x\right)$ or $u(x,y)=f_1\left(2Cx+\left(B+\sqrt{B^2-4AC}\right)y\right)+f_2\left(2Cx-\left(B+\sqrt{B^2-4AC}\right)y\right)$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.